The other welfare : supplemental security income and U.S. social policy - Berkowitz, Edward D.; DeWitt, Larry, 1949- (UPCC book collections on Project MUSE. Political Science and Policy Studies., 2013)
This title offers a comprehensive history of Supplemental Security Income (SSI), from its origins as part of President Nixon's daring social reform efforts to its pivotal role in the politics of the Clinton administration.